التأصيل الفقهي للكفالة البنكية وأخذ الأجرة عليها (دراسة فقهية): Jurisprudential rooting of the bank guarantee and taking the fee for it (jurisprudential study) (Khairulummah, 2022)
This study aims to explain the definition of guarantee linguistically and idiomatically, and to clarify its pillars for jurists and its legitimacy so that its concept can be fully known, and to mention some provisions of guarantee that help in understanding the subject and to explain the jurisprudential adaptation of “bank guarantee” so that its facts and ambiguities become clear in the light of Islamic law; Because knowing its ruling is based on it, and reviewing the ideas of scholars and their opinions regarding this issue (the ruling on the bank guarantee and taking the rent or fees for it) with mentioning their evidence for what they deduce from it, and the discussion and the most correct saying in it, and referring to the decisions and fatwas that were issued in it by the scientific bodies and jurisprudence councils at the time the present.
Keywords: bank guarantee, Islamic banks, and Islamic jurisprudence.